Adapting the WHO Safe Childbirth Checklist: A collaborative study in West Africa - Kadidiatou R. Kourouma; Tieba Millogo; Aissatou Diallo; Wambi M.E. Yaméogo; Marie L. Agbré-Yacé; Mamadou D. Baldé; Issaka Tiembré; Alexandre Delamou; Séni Kouanda (Journal of Public Health in Africa)
Background: The World Health Organization Safe Childbirth Checklist (WHO SCC) was developed to increase the uptake of essential birth practices; however, only a few studies have adopted this process in French West African countries.